Strategi Pedagogis dalam Pembelajaran Kitab Nailur Roja Syarah Safinatun Najah pada Bab Nikah di Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta - Agus Afriyal; Alin Dwi Setyani; Imam Maulana Azis; Gestian Adi Irawan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the pedagogical strategies in teaching Nailur Roja Syarah Safinatun Najah, particularly the chapter on marriage, at Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta. The teaching of classical Islamic texts (kitab kuning) in pesantren not only emphasizes textual understanding but also requires adaptive strategies to ensure that marriage laws are comprehended both theoretically and practically. This research employed a descriptive qualitative method, with data collected through interviews with students and teachers, as well as library research on classical Islamic texts, pesantren pedagogy, and Islamic marriage law. The findings show that pedagogical strategies combine traditional methods such as bandongan and sorogan with contextual approaches including interactive discussions, group deliberations, and case-based learning. The main challenges for students are difficulties in understanding classical Arabic and relating the material to the contemporary Indonesian legal context. To overcome these issues, teachers provide simplified explanations, use real-life analogies, and encourage active student participation. Therefore, the applied pedagogical strategies effectively enhance students’ comprehension of the marriage chapter both normatively and practically.